Hormonal and biochemical changes in elite basketball players during a 4-week training camp - Hoffman, J. R.; Epstein, S.; Yarom, Y.; Zigel, L.; Einbinder, M. (The Journal of Strength and Conditioning Research, 1999)
This investigation examined hormonal and biochemical changes in basketball players during a 4-week training camp before the European championships. Ten members of the Israel national team (mean ± SD; age: 26.4 ± 4.3 years; weight: 100.7 ± 12.3 kg; and height: 196.4 ± 8.0 cm) participated in this study, which began 4 weeks after the regular season. Plasma samples of testosterone, cortisol, luteinizing hormone, thyroid-stimulating hormone, triiodothyronine, free thyroxine, creatine kinase, and urea were obtained before (T1) and after 9 (T2), 17 (T3), and 28 (T4) days of practice. Questionnaires concerning appetite, quality of sleep, muscle soreness, and recovery time following practice were filled out before each blood draw. Differences (p < 0.05) in the volume of training were seen between T1 and T2 (150 ± 29 min·d1) and T3 and T4 (92 ± 28 min·d1). Muscle soreness and recovery time following practice were greater (p < 0.05) at T2 than T1, T3, and T4. A significant increase in cortisol, although remaining within normal physiological range, was observed between T1 (260 ± 91 nmol·L1) and T4 (457 ± 99 nmol·L1). No changes from T1 were seen in testosterone (14.2 ± 5.6 nmol·L1), luteinizing hormone (4.2 ± 1.6 IU·ml1), creatine kinase, and urea or in the testosterone-to-cortisol ratio. In addition, no significant changes from T1 were observed in any of the thyroid hormones. These results suggest that a 28-day training camp may not cause significant disturbances in hormonal or biochemical stress markers in elite athletes.